Women and violence in the patriarchal legal system of the Hispanic Monarch (s. XVI-XVII) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2021)
In the Sixteenth and Seventeenth Centuries, in the territory of the Hispanic Monarchy, the territorial and people particularisms, which characterized medieval law, persisted in the private jurisdictions that social and power groups, through the male heads of the family, wielded to affirm their power around their Families, Houses and Lineages. We will present brief stories, emanating from judicial files, on situations of violence exercised in the body of women and their legal resolution.
Keywords: Justice; Women; Patriarchal violence